Edukasi Ekonomi Kreatif Jahe Celup Desa Grogolan - Findayani, Aprilia; Astuti, Findhi; Salsabila, Amanda (Jurnal Bina Desa, 2025)
The income of the people of Grogolan Village only depends on rice crops, therefore the community needs to innovate so that the village changes. The Giat 9 UNNES team raised ginger to be made into dipped ginger that is created from packaging and presentation by paying attention to the principles of creative economy, to improve the economic standard of life in Grogolan Village. The Giat 9 UNNES team collaborated with the cadre mothers of each hamlet of Grogolan Village in the ginger dipping program, so that all cadre mothers present were able to become spokespersons for the Grogolan Village community. The ingredients needed to make ginger dipping are very easy to find in the community, namely, ginger as the main component, cinnamon and lemongrass. The tools needed are a chopper or blender, tea bags, ziplock plastic and brand stickers. The stages of making ginger dip, through the process of selecting, peeling, washing, cutting, and drying in the sun. The Giat 9 UNNES team conducted exposure, socialization, and assistance to cadre mothers for the ginger dipping stage, the team also tried to plan as much and as practical as possible so that the community could apply it well.